2004
DOI: 10.1038/sj.ejhg.5201351
|View full text |Cite
|
Sign up to set email alerts
|

Association of BDNF with restricting anorexia nervosa and minimum body mass index: a family-based association study of eight European populations

Abstract: Eating disorders (ED), such as anorexia nervosa (AN) and bulimia nervosa (BN), are complex psychiatric disorders where different genetic and environmental factors are involved. Several lines of evidence support that brain-derived neurotrophic factor (BDNF) plays an essential role in eating behaviour and that alterations on this neurotrophic system participates in the susceptibility to both AN and BN. Accordingly, intraventricular administration of BDNF in rats determines food starvation and body weight loss, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
3
6

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 130 publications
(93 citation statements)
references
References 27 publications
4
80
3
6
Order By: Relevance
“…On the other side, this method is much less cost-effective than a case-control design (Gorwood, 1999). Our results are obviously limited by the relatively small number of family trios and a recent european family study including 453 trios also reports the association between anorexia nervosa and the Met66 allele (Ribases et al, 2005b). Several findings suggest that BDNF and its high affinity receptor TrkB contribute to food intake and body weight control.…”
Section: Discussionmentioning
confidence: 69%
“…On the other side, this method is much less cost-effective than a case-control design (Gorwood, 1999). Our results are obviously limited by the relatively small number of family trios and a recent european family study including 453 trios also reports the association between anorexia nervosa and the Met66 allele (Ribases et al, 2005b). Several findings suggest that BDNF and its high affinity receptor TrkB contribute to food intake and body weight control.…”
Section: Discussionmentioning
confidence: 69%
“…OCPD ϭ obsessive-compulsive personality disorder. Shafran, 2003), other research finds support for the distinction in epidemiological, genetic, and descriptive studies (e.g., Ribases et al, 2004Ribases et al, , 2005. In this review, we indicate where subtypes are differentiated and highlight future directions for research with consideration of these subtypes.…”
Section: Premorbid Social Functioningmentioning
confidence: 76%
“…Observations of altered feeding behavior leading to increased body weight in brain-derived neurotrophic factor (BDNF) knockout mice and reports that intraventricular administration of BDNF in rats resulted in reduced feeding and weight loss prompted Ribases et al (2003) to study the BDNF gene in AN. The investigators observed a strong association between restricting AN, as well as minimum body weight, and an amino acid substitution within the BDNF precursor protein (Val66Met); they replicated the findings in an independent sample (Ribases et al 2005). Because the BNDF mutation would be expected to increase food intake, the finding appears counterintuitive.…”
Section: Animal Models Of Anmentioning
confidence: 78%